Dealing with Crisis The Japanese Experience and Beyond - Babb, James; Iida, Takashi (Edward Elgar Publishing, 2023)
Reflecting on the depth of the experience with crises, this innovative book demonstrates what the world can learn from insights into crises from the Japanese perspective. Taking an institutionalist approach with a strong historical precedent, leading scholars in the social sciences and law explore how better to deal with foreseeable and unforeseen crises.